A novel protein encoded by the circular form of the SHPRH gene suppresses glioma tumorigenesis - Zhang, Maolei; Huang, Nunu; Yang, Xuesong; Luo, Jingyan; Yan, Sheng; Xiao, Feizhe; Chen, Wenping; Gao, Xinya; Zhao, Kun; Zhou, Huangkai; Li, Ziqiang; Ming, Liu; et al. (Oncogene, 2018)
Circular RNAs (circRNAs) are recognized as functional non-coding transcripts in eukaryotic cells. Recent evidence has indicated that even though circRNAs are generally expressed at low levels, they may be involved in many physiological or pathological processes, such as gene regulation, tissue development and carcinogenesis. Although the ‘microRNA sponge’ function is well characterized, most circRNAs do not contain perfect trapping sites for microRNAs, which suggests the possibility that circRNAs have functions that have not yet been defined. In this study, we show that a circRNA containing an open reading frame (ORF) driven by the internal ribosome entry site (IRES) can translate a functional protein. The circular form of the SNF2 histone linker PHD RING helicase (SHPRH) gene encodes a novel protein that we termed SHPRH-146aa. Circular SHPRH (circ-SHPRH) uses overlapping genetic codes to generate a ‘UGA’ stop codon, which results in the translation of the 17 kDa SHPRH-146aa. Both circ-SHPRH and SHPRH-146aa are abundantly expressed in normal human brains and are down-regulated in glioblastoma. The overexpression of SHPRH-146aa in U251 and U373 glioblastoma cells reduces their malignant behavior and tumorigenicity in vitro and in vivo. Mechanistically, SHPRH-146aa protects full-length SHPRH from degradation by the ubiquitin proteasome. Stabilized SHPRH sequentially ubiquitinates proliferating cell nuclear antigen (PCNA) as an E3 ligase, leading to inhibited cell proliferation and tumorigenicity. Our findings provide a novel perspective regarding circRNA function in physiological and pathological processes. Specifically, SHPRH-146aa generated from overlapping genetic codes of circ-SHPRH is a tumor suppressor in human glioblastoma.